Lattice Stabilized and Emission Tunable Pure‐Bromide Quasi‐2D Perovskite for Air‐Processed Blue Light‐Emitting Diodes - Yangyang Guo; Penghui Yang; Fan Dong; Huixin Li; Jialiang Gao; Zeyi Cheng; Jiandong Wu; Yadong Xu; Hongyue Wang; Hongqiang Wang (Advanced Science)
Abstract Realizing air‐processed blue halide perovskite films with tailored emission is significant for promoting the commercialization of perovskite light‐emitting diodes (PeLEDs). However, the intrinsically inferior thermodynamic stability and laborious crystallization kinetics control under humidity interference limit the fabrication of blue perovskite emitters in ambient air. Here, air‐processed pure‐bromide quasi‐2D blue perovskite films are achieved with stabilized lattice and tunable emission by interstitial doping of trivalent metallic cations. This strategy improves the formation energy of the perovskite lattice, promotes energy transfer between different n phases, and suppresses intrinsic electron‐phonon coupling in the perovskite films. The emission‐controllable blue PeLEDs are fabricated in ambient air for the first time. The champion deep blue PeLED shows maximum external quantum efficiency (EQE) of 2.05% and luminance of 246.56 cd m−2, which are comparable to the state‐of‐the‐art of similar devices fabricated in glovebox. The work pioneers a simple method of electronic structure engineering to tune the emission of air‐processed blue perovskite, breaking the limitations of thermodynamic stability and crystallization kinetics control of perovskite in ambient air.